Influence of Chronotype and Theobromine on the 24-h Variation in Peak Expiratory Flow Rate in Healthy Adults - Anika Köhlmoos; Manuela Dittmar (Journal of Circadian Rhythms)
The influence of morningness-eveningness preference and dietary components on the circadian variation in peak expiratory flow (PEF), an established criterion for pulmonary function, is not fully understood. This study aimed to investigate (a) how the chronotype influences the 24-h variation in PEF and (b) whether the bronchodilator theobromine affects this variation differently in different chronotypes. Ninety-seven healthy non-smoking females (54 early chronotypes, ET; 43 late chronotypes, LT; 18–35 years) recorded their PEF over 24 hours at 4-h intervals (08:00/12:00/16:00/20:00/24:00/04:00/08:00 h). In a subgroup (26 ET, 18 LT), the effect of 48 mg theobromine (40 g dark chocolate) on PEF was compared on three consecutive 24-h days with no administration, morning administration and evening administration of theobromine. Repeated measures ANOVA tested for 24-h variation in PEF. Both chronotypes displayed significant 24-h variation in PEF (P < 0.0001) explaining 36% (ET) and 31% (LT) of variance of PEF. The time of maximum PEF was three hours earlier in ET than in LT (P = 0.003) and correlated negatively with chronotype scores (P = 0.001) and positively with bedtimes (awakening time: P < 0.001; sleep-onset time: P = 0.012). The chronotypes showed no differences in 24-h mean and amplitude % mean for PEF. Administration of theobromine strengthened the morning increase (P = 0.004) and weakened the evening decrease (P = 0.063) of PEF in LT, but had no effect in ET. The differences found between chronotypes in timing of maximum PEF and responsiveness to the bronchodilator theobromine might have clinical relevance. Therapy for respiratory diseases should consider the chronotype of patients for drug timing and dosage.